Good character at school: positive classroom behavior mediates the link between character strengths and school achievement - Wagner, Lisa; Ruch, Willibald (Frontiers in Psychology, 2015)
Character strengths have been found to be substantially related to children’s and adolescents’ well-being. Initial evidence suggests that they also matter for school success (e.g., Weber and Ruch, 2012). The present set of two studies aimed at replicating and extending these findings in two different age groups, primary school students (N = 179; mean age = 11.6 years) and secondary school students (N = 199; mean age = 14.4 years). The students completed the VIA-Youth, a self-report measure of the 24 character strengths in the VIA classification. Their teachers rated the students’ positive behavior in the classroom. Additionally, school achievement was assessed: For the primary school students (Study 1), teachers rated the students’ overall school achievement and for the secondary school students (Study 2), we used their grades as a measure of school achievement. We found that several character strengths were associated with both positive classroom behavior and school achievement. Across both samples school achievement was correlated with love of learning, perseverance, zest, gratitude, hope, and perspective. The strongest correlations with positive classroom behavior were found for perseverance, self-regulation, prudence, social intelligence, and hope. For both samples, there were indirect effects of most of the character strengths on school achievement through teacher-rated positive classroom behavior. The converging findings from the two samples support the notion that character strengths contribute to positive classroom behavior, which in turn enhances school achievement. Results are discussed in terms of their implications for future research and for school interventions based on character strengths.